Implementation of Eco-pesantren through green building concept at Pesantren Modern Inshafuddin, Banda Aceh, Indonesia / Sitti Sausan Maulida, Cut Nursaniah and Laina Hilma Sari - Maulida, Sitti Sausan; Nursaniah, Cut; Sari, Laina Hilma (Universiti Teknologi MARA, Perak, 2025)
Green building is the key to reducing negative impacts on the environment, as well as playing a role in encouraging environmental awareness and producing environmentally friendly behaviors. It is important to review the building facilities at Pesantren Modern Inshafuddin (PMI) to support the activities and implementation of eco-pesantren, so that they can become an example of an environmentally friendly Islamic boarding school model. This research aims to see the potential and formulate strategies for improving building quality and environmentally friendly practices to support the Eco-pesantren concept at PMI. Data collection techniques were by using observation methods, questionnaires, interviews and documentation. The research method uses Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis techniques. The research results show that PMI has potential strengths and opportunities in terms of development to support the implementation of the eco-pesantren concept. Strategies that can be implemented are: 1) carrying out plans to repair and increase the quality of buildings in order to achieve environmentally friendly building concept standards, such as providing rainwater storage, providing used water waste treatment for recycling, greening the PI environment, utilizing renewable energy, and re-providing waste banks; 2) empowering all students in environmentally friendly practices in daily activities to increase awareness and realize environmentally cultured character; 3) utilize existing land to support the implementation of the Eco-pesantren concept for planting activities, such as creating a living pharmacy garden as an area for teaching materials and environmental practice and creating biopore wells to manage rainwater.